Automated vehicle crash sequences: Patterns and potential uses in safety testing. (April 2021) - Song, Yu; Chitturi, Madhav V.; Noyce, David A.
Highlights: Sequence of events data from five years (2015-2019) of California automated vehicle (AV) crash reports were analyzed. The most representative subsequence was "collision following AV stop". Disengagements were observed in 24% of AV crash sequences and were mostly (68%) followed by immediate collisions between the AV and other road users/objects. Crash sequences clustered into seven groups, each with a distinctive representative subsequence, presenting unique dynamics in AV crash progression. AV crash sequence groups were significantly associated with crash outcome and environmental condition variables. AV crash sequences have potential uses in developing AV test scenarios and be embedded as a core component of proposed scenario-based AV safety testing framework. Abstract: With safety being one of the primary motivations for developing automated vehicles (AVs), extensive field and simulation tests are being carried out to ensure AVs can operate safely on roadways. Since 2014, the California Department of Motor Vehicles (DMV) has been collecting AV collision and disengagement reports, which are valuable data sources for studying AV crash patterns. A crash sequence of events describes the AV's interactions with other road users before a collision in a temporal manner. In this study, sequence of events data extracted from California AV collision reports were used to investigate patterns and how they may be used to develop AV test scenarios. Employing sequence analysis methods and clustering, this study evaluated 168 AV crashes (with AV in automatic driving mode before disengagement or collision) reported to the California DMV from 2015 to 2019. Analysis of subsequences showed that the most representative pattern in AV crashes was "collision following AV stop". Analysis of event transition showed that disengagement, as an event in 24% of all studied AV crash sequences, had a transition probability of 68% to an immediate collision. Cluster analysis characterized AV crash sequences into seven groups with distinctive crash dynamic features. Cross-tabulation analysis showed that sequence groups were significantly associated with variables measuring crash outcomes and describing environmental conditions. Crash sequences are useful for developing AV test scenarios. Based on the findings, a scenario-based AV safety testing framework was proposed with sequence of events embedded as a core component.